2016
DOI: 10.1186/s12905-016-0283-9
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of unmet need for family planning among women in Urban Cameroon: a cross sectional survey in the Biyem-Assi Health District, Yaoundé

Abstract: BackgroundWith the unacceptably high level of unmet need for family planning in Sub-Saharan Africa, reducing unmet need is paramount in the fight against the high levels of induced abortions, maternal and neonatal morbi-mortality. A clear understanding of the determinants of unmet need for family planning is indispensable in this light. The objective of this study was to determine the prevalence of unmet need for family planning in Urban Cameroon while identifying major determinants of unmet need among women i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

19
83
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(109 citation statements)
references
References 9 publications
19
83
6
1
Order By: Relevance
“…About 225 million women in low and middleincome countries have an unmet need for a modern method of family planning with the highest unmet need being in Sub-Saharan Africa [1][2][3]. Discounting the partial protection from lactational amenorrhea, unmet need for family planning is particularly high among postpartum women [4] resulting in high levels of unintended pregnancies (estimated 73 million in 2012 [5]) especially in low and middle income countries.…”
Section: Introductionmentioning
confidence: 99%
“…About 225 million women in low and middleincome countries have an unmet need for a modern method of family planning with the highest unmet need being in Sub-Saharan Africa [1][2][3]. Discounting the partial protection from lactational amenorrhea, unmet need for family planning is particularly high among postpartum women [4] resulting in high levels of unintended pregnancies (estimated 73 million in 2012 [5]) especially in low and middle income countries.…”
Section: Introductionmentioning
confidence: 99%
“…[39][40][41] Women who planned pregnancy were also found in the present study to have positive attitude toward the use of family planning, which was also discussed in several unmet family planning needs studies. 42 The present study showed that about 34% of women did not plan their current pregnancy, 28% want to postpone this pregnancy for one to three years, while the rest welling to limit their number of children. According to the definition of unmet family planning need; this is considered unplanned pregnancy of the current or last pregnancy.…”
mentioning
confidence: 99%
“…According to the definition of unmet family planning need; this is considered unplanned pregnancy of the current or last pregnancy. 42 Fear of side effect was found to be one of the major women's concerns for none use of contraceptives in several studies as an important reason to stop using contraceptives. [42][43][44][45][46] In this study, women fear from side effects might be related to misinformation because the main source of information they get is not from the health care provider.…”
mentioning
confidence: 99%
See 2 more Smart Citations